FABRIKASI OF Fe3O4/ZnO NANOCOMPOSITE BY ULTRASONICATION METHOD AND ITS APPLICATION FOR ANTIBACTERIAL - Oktavia, Anggraini Dwi; Rohmawati, Lydia (Universitas Mataram, 2022)
The spread of diseases caused by bacteria seriously threatens human health. Alternative materials with antibacterial effects are needed to overcome this problem, such as Fe3O4/ZnO. This study aims to determine the activity of the antibacterial inhibition zone on Fe3O4/ZnO nanocomposites. The Fe3O4/ZnO nanocomposite fabrication used the ultrasonication wave method. Characterization was performed using X-ray diffraction (XRD), Fourier Transforms Infrared (FTIR), and antibacterial activity tests. The results of the XRD analysis showed that the average crystal size was about 42 nm for Fe3O4, 36 nm for ZnO, and 39 nm for Fe3O4/ZnO. The FTIR results on the nanocomposite showed the characteristics of the Fe-O group at the absorption peak of 874.93 and 691.29 cm-1, while at 436.56 cm-1 indicated the presence of Zn-O compound bonds. The Fe3O4/ZnO nanocomposite with a weight ratio (1:10) showed good effectiveness in inhibiting S. aureus and E. coli bacteria at concentrations of 0.8 mg/m and 1 mg/ml. Meanwhile, in E. coli bacteria, the average diameter of the inhibition zone was relatively low. Thus Fe3O4/ZnO nanocomposite has the potential to be applied in antibacterial applications